References and benchmarks for pore-scale flow simulated using micro-CT images of porous media and digital rocks. (November 2017) - Saxena, Nishank; Hofmann, Ronny; Alpak, Faruk O.; Berg, Steffen; Dietderich, Jesse; Agarwal, Umang; Tandon, Kunj; Hunter, Sander; Freeman, Justin; Wilson, Ove Bjorn
Highlights: We generate a reference dataset to quantify the impact of numerical solvers, boundary conditions, and simulation platforms. We consider a variety of microstructures ranging from idealized pipes to digital rocks (36 in total). Multiple numerical engines are included, e.g., LBM, fluid dynamics, voxel based, semi-analytical, and known empirical models. We notice relatively larger variability in computed permeability of digital rocks with coefficient of variation (up to 25%). Differences are due to boundary conditions, convergence criteria, and parameterization of physics equations. Abstract: We generate a novel reference dataset to quantify the impact of numerical solvers, boundary conditions, and simulation platforms. We consider a variety of microstructures ranging from idealized pipes to digital rocks. Pore throats of the digital rocks considered are large enough to be well resolved with state-of-the-art micro-computerized tomography technology. Permeability is computed using multiple numerical engines, 12 in total, including, Lattice-Boltzmann, computational fluid dynamics, voxel based, fast semi-analytical, and known empirical models. Thus, we provide a measure of uncertainty associated with flow computations of digital media. Moreover, the reference and standards dataset generated is the first of its kind and can be used to test and improve new fluid flow algorithms. We find that there is an overall good agreement between solvers for idealized cross-section shape pipes. As expected, the disagreement increases with increase in complexity of the pore space. Numerical solutions for pipes with sinusoidal variation of cross section show larger variability compared to pipes of constant cross-section shapes. We notice relatively larger variability in computed permeability of digital rocks with coefficient of variation (of up to 25%) in computed values between various solvers. Still, these differences are small given other subsurface uncertainties. The observed differences between solvers can be attributed to several causes including, differences in boundary conditions, numerical convergence criteria, and parameterization of fundamental physics equations. Solvers that perform additional meshing of irregular pore shapes require an additional step in practical workflows which involves skill and can introduce further uncertainty. Computation times for digital rocks vary from minutes to several days depending on the algorithm and available computational resources. We find that more stringent convergence criteria can improve solver accuracy but at the expense of longer computation time.